A contribuição da economia criativa no processo de implementação do ESG nas empresas: um modelo sugestivo ESG - Stevanato, Ana Marcilia dos Santos (2023)
The study called “The contribution of the Creative Economy in the process of implementing ESG in companies: a suggestive model ESG”, seeks to answer the problem that revolves around the difficulty faced by companies in adopting genuine actions of environmental, social and social responsibility. governance in its operations and procedures. This work assumes that the Creative Economy can serve as a driving force in behavior inspired by ESG and contribute to the elaboration of a model of good practices and recommendations, in order to help companies to adopt actions in the environmental, social and social spheres. governance more effectively, avoiding falling into the trap of greenwashing. For carrying out the research, methodological procedures are being considered that use exploratory bibliographical research to explain the concepts and central themes; as well as content analysis based on documentary exploration; case study and interview in two companies that use Creative Economy practices and, consequently, implement actions that permeate the ESG factors, in an exemplary manner. The choice of theme becomes relevant as the global economic scenario, driven by the pandemic, climate change and the new form of consumption, forces companies to assume a role of not only economic responsibility, but also socio-environmental and governance. Accordingly, there is a growing awareness that, in order to remain productive, competitive and healthy, companies must maintain a good relationship and a positive image with their investors and customers.